KARAKTERISTIK FISIK LAHAN DI NAGARI PARU (RIMBO LARANGAN) KABUPATEN SIJUNJUNG - Putra Ulni, Arie Zella (Jurnal Spasial, 2015)
Indonesia is a country that has a tropical climate, tropical climate caused so much rain during the year compared to the dry season. With the tropical climate of Indonesia has a region dominated by forests that are the lungs of the world. One of the existing forests are forests located in the District Lung Nagari Sijunjung Sijunjung or better known by local people with the name Rimbo Prohibition. This study aims to find out about the physical karaksteristik land (slope, landform, hydrology) in Rimbo Prohibition in Nagari Lung District of Sijunjung Sijunjung, knowing how the utilization of land by the community around Rimbo Prohibition. This type of research is descriptive. The results showed that the physical characteristics of the land is very varied Prohibition Rimbo, Rimbo height of Prohibition highly variable, then the slope in Rimbo Laranagn also vary. Landform in Rimbo ban can be divided into three parts, namely the karst hills, alluvial plains and natural levee. Hydrological conditions in the sub-basins of lung depends on the streams flowing from Rimbo Prohibition. Land use specially designated as forests. With Prohibition Rimbo characteristics that vary widely made public memamfaatkan forest products as needed to make Rimbo Prohibition awake d beauty.Keywords: physical characteristics of the land, the use of Rimbo Prohibition